1979
DOI: 10.1038/ki.1979.149
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular transport of gentamicin in the rat

Abstract: The renal handling of gentamicin in the rat was examined by clearance, microinjection, and renal cortical-slice techniques. The steady-state renal clearance of 14C-gentamicin, when corrected for the 7.5% binding to plasma protein, was not significantly different from that of 3H-inulin. At the end of the renal clearance experiments, the cortical concentration of gentamicin was 93 +/- 7 microgram/g of tissue (N = 7), a concentration threefold greater than that of the medulla and 20-fold greater than that of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…However, gentamicin may cause a dose-dependent nephrotoxicity (Bennett, 1997). Previous studies have shown that gentamicin is mainly concentrated in the proximal tubular cells, and the resultant renal dysfunction may be recognized as Fanconi-like syndrome of a proximal tubular damage (Pastoriza-Munoz et al, 1979;Gainza et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, gentamicin may cause a dose-dependent nephrotoxicity (Bennett, 1997). Previous studies have shown that gentamicin is mainly concentrated in the proximal tubular cells, and the resultant renal dysfunction may be recognized as Fanconi-like syndrome of a proximal tubular damage (Pastoriza-Munoz et al, 1979;Gainza et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The nephrotoxicity of these drugs is associated with selective accumulation of aminoglycosides in the kidney, with cortical levels reaching as high as 20 times the circulating levels in serum (10,40). Aminoglycosides are known to accumulate in renal tissue via tubular reabsorption as well as by extraction from the circulation at the basolateral surface of the kidney, although brush border uptake is thought to contribute more on a quantitative basis (6,7,17,34). However, it remains to be established whether the nephrotoxicity is a consequence of accumulated drug or relates to an interaction at the initial point of contact between the renal cell and the aminoglycoside, the plasma membrane.…”
mentioning
confidence: 99%
“…membrane (pasturiza-Munoze et al, 1979). DnJg accumulation into lysosomes can be demonstrated by autoradiography (Silverblatt and Kuehn, 1979) or by Immunogold labeling (Beauchamp et a/., 1991) and may reach concentrations that are several-fold higher than the nonnal serum levels (Giuliano et al, 1984).…”
Section: Development and Patbology Of Nepbrotodcitymentioning
confidence: 99%